The Meaning and Determinants of Workplace Happiness among Outsourced Employees: A Phenomenological Study at Indonesian State Universities - Rahmandaru Fran Adeastra; Siti Rohmah Nurhayati; Rahman Pranovri Putra (Da'wa Faculty of Islamic State University Salatiga, 2025)
Happiness at work has proven to be important for both companies and employees. However, outsourcing employees are faced with conditions that do not support happiness at work, such as: (1) job insecurity, (2) status conflicts, and (3) no career path. This research aims to explore the meaning of happiness at work for outsourcing employees and determine the factors that can influence it. This research used a qualitative phenomenological method with 5 outsourcing employees who were placed to work at one of the state universities in Indonesia as resource persons. Data were collected using semi-structured interviews and data analysis using interpretative phenomenological analysis (IPA). The research results show that the meaning of happiness at work for outsourced employees is when they have a job amidst limited job opportunities. They are happy because they can earn a living to meet their family's needs without losing their main role in the family. They feel happy at work when there are good relationships with coworkers and gain recognition from the work environment. The research results show 5 factors that influence happiness at work, namely: (1) Relationships with coworkers, (2) Work Environment, (3) Difficulties faced, (4) Evaluation of the company, and (5) Gratitude. As the outsourcing system continues to develop, more and more workers will have outsourcing employee status. These findings fill the gap in literature/information related to workplace happiness among outsourced employees so that they can be used as material for consideration by policy makers in companies and in government.